Multi‐stage coordinated operation of a multi‐energy microgrid with residential demand response under diverse uncertainties - Yumin Chen; Xue Feng; Zhengmao Li; Yan Xu; Amir Miragha (Energy Conversion and Economics, 2020)
Abstract This paper presents a two‐stage stochastic operation method for a multi‐energy microgrid (MEMG). The method can optimally schedule distributed generators, electric boilers, electrical chillers, and storage devices under the system technical constraints. Various uncertainties from renewable energy generation, electricity tariff, and load demands are handled by this method. At the same time, the indoor temperature is controlled to guarantee the thermal comfort of customers. At the first stage, the unit commitment of all generators and charging/discharging power of energy storage devices are obtained. At the second stage, real‐time generation outputs from the generators are optimized given the uncertainty realization. The developed model is formulated as a mixed‐integer linear programming (MILP) problem with the objective of minimizing the daily operating cost. Several case studies are carried out to examine the effectiveness and performance of the proposed method. Simulation results show that the proposed method can effectively save the operational cost and, at the same time, maintain the robustness of the MEMG and customers’ thermal comfort.